2012
DOI: 10.1155/2012/635312
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Modifying Lumbopelvic Motion during Hip Medial Rotation in People with Low Back Pain

Abstract: Reducing increased or early lumbopelvic motion during trunk or limb movements may be an important component of low back pain treatment. The ability to reduce lumbopelvic motion may be influenced by gender. The purpose of the current study was to examine the effect of gender on the ability of people with low back pain to reduce lumbopelvic motion during hip medial rotation following physical therapy treatment. Lumbopelvic rotation and hip rotation before the start of lumbopelvic rotation were assessed pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The without LBP [59][60][61]. Nevertheless, it was suggested that gender differences may not be relevant when subgrouping subjects by different patterns of lumbar posture and movements [62].…”
Section: Discussionmentioning
confidence: 99%
“…The without LBP [59][60][61]. Nevertheless, it was suggested that gender differences may not be relevant when subgrouping subjects by different patterns of lumbar posture and movements [62].…”
Section: Discussionmentioning
confidence: 99%
“…No earlier study has investigated whether middleaged men have less ability to control flexion movements in the trunk than do women. A study examining the effect of sex on the ability of adults with LBP to reduce lumbo-pelvic motion, however, showed that men demonstrated greater lumbo-pelvic rotation and less hip rotation during lumbopelvic rotation than did women, 31 indicating that there are Bold numbers indicate a significant (P < 0.05) difference between men and women. …”
Section: Discussionmentioning
confidence: 99%
“…1 and 2). 27,28 The collected data were filtered with Butterworth low pass filter with cut off frequency of 2 Hz. The initial and terminal point of motion for pelvic and lower extremity segments were determined based on previous study.…”
Section: Kinematic Measurement and Processingmentioning
confidence: 99%